Interface between immune and nerve systems: Neuroendocrine axis of stress - Haour, F. (First international symposium sciences and practices in swimming, 2006)
Theoretical review on the interface between the immune system and the nerve system as well as on the neuroendocrine axis of stress: The immune system, the concept of stress, the neuroendocrine axis of stress, consequences of the activation of the axis of stress, on the immune system, local regulations and functional loop of retroaction, pathologic implications and conclusions.